2017
DOI: 10.1002/smll.201700841
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hyperthermia: Spatiotemporal Protein Unfolding and Inactivation by Nanosecond Plasmonic Heating

Abstract: Spatiotemporal control of protein structure and activity in biological systems has important and broad implications in biomedical sciences as evidenced by recent advances in optogenetic approaches. Here, this study demonstrates that nanosecond pulsed laser heating of gold nanoparticles (GNP) leads to an ultrahigh and ultrashort temperature increase, coined as “molecular hyperthermia”, which causes selective unfolding and inactivation of proteins adjacent to the GNP. Protein inactivation is highly dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…Carbon The very local increase in temperature may be also of interest to control the structure and folding/unfolding of proteins; indeed, Kang et al reported that in the immediate adjacent environment of AuNPs illuminated with a pulsed-laser, proteins can be denatured [104]. This interesting feature could find applications to treat diseases involving protein unfolding and aggregation.…”
Section: Lightmentioning
confidence: 99%
“…Carbon The very local increase in temperature may be also of interest to control the structure and folding/unfolding of proteins; indeed, Kang et al reported that in the immediate adjacent environment of AuNPs illuminated with a pulsed-laser, proteins can be denatured [104]. This interesting feature could find applications to treat diseases involving protein unfolding and aggregation.…”
Section: Lightmentioning
confidence: 99%
“…It can also selectively damage deoxyribonucleic acid (DNA) in cancer cells 3 , while avoiding the damage to the healthy tissue. Recently, it was shown that the application of hyperthermia can be extended to the subcellular domain 4 .…”
Section: Microscale Direct Measurement Of Localized Photothermal Heatmentioning
confidence: 99%
“…Such models, along with efficient numerical procedures for their implementations, were developed before in the context ultrashortpulsed lasers (e.g., [13][14][15]), with an increasing range of medical applications currently in place. A number of them are connected with nanosecond pulsed laser heating techniques [16], as well as with thermoplasmonics applications in medicine [17], where the goal is to create highly specific therapies by inactivating dysfunctional protein molecules (the field known as molecular hyperthermia). Another avenue for an extension of the current model is to account for the finite speed of heat propagation through thermal relaxation models (e.g., [18][19]).…”
Section: Mathematical Modeling Of the Rfa Proceduresmentioning
confidence: 99%